Perancangan Server Kantor Desa Tomuan Holbung Berbasis Client Server - Chairul Rizal; Supiyandi Supiyandi; Muhammad Zen; Muhammad Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Abstract− In the era of regional autonomy, the village is a very important part in determining the success of development and in direct contact with the community, especially in public services. Server is a medium that has an important role to provide internet access services for its users. So that the network can be used optimally, it is necessary to have a server. This study aims to design a server in the Tomuan Holbung Village Office, Asahan Regency by building an efficient, flexible server infrastructure and optimizing resource use, so that it can be adjusted to the workload so that hardware resources are optimal. This research was conducted to be a solution for the use of hardware resources provided by the Server machine that has not been used optimally, so efficient steps are needed to overcome this problem. The results of the research obtained are in the form of server design and optimizing the use of resources and managing servers efficiently in terms of time and cost.